Affect in the context of self-determination theory - Hagger, Martin; Protogerou, C. (2018)
© Oxford University Press 2018. All rights reserved. Self-determination theory has been applied to understand the role of affect in motivation and behavior in health contexts. According to self-determination theory, autonomous forms of motivation, reflecting self-endorsed reasons for acting and the satisfaction of psychological needs, are related to participation and persistence in health behavior. Research examining the role of affect in determining health behavior from the perspective of the theory is relatively sparse. Affect has served as both an outcome and process in applications of the theory to health behavior. Positive affect and psychological well-being have been identified as important outcomes of participating in behaviors for autonomous reasons. Affect is inextricably linked to motivational processes through eudaimonic and hedonic well-being, the passionate pursuit of activities, and the regulation of behavior through active management of aversive emotional responses. The chapter outlines how support for autonomous motivation by significant others may lead to adaptive behavioral engagement and affective responses in health behavior.